Application of core X-ray microtomography in oilfield geology - A. A. Ponomarev; M. D. Zavatsky; T. S. Nurullina; M. A. Kadyrov; K. A. Galinsky; O. A. Tugushev (Georesursy, 2024)
The article presents studies devoted to the practical application of computer X-ray microtomography (micro-CT) in oilfield geology. In particular, the authors give results of using the method for sample defectoscopy before petrophysical studies in order to improve the quality of analyzes. The paper includes an example of assessing the depth of core plugging with drilling fluid; assessing the mineral composition by micro-CT; experimental core studies when modeling the thermal effect on the oil source rocks of the Bazhenov formation. The authors also examine the current state of research in the field of digital petrophysics or digital core. The study is aimed at introducing the micro-CT method into the oilfield process.